Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar PKN Siswa Kelas IV SD Negeri 106156 Klumpang - Lubis, Fanny Claudia; Hariati, Emy; Harahap, Syarifah Ainun (Medan Resource Center, 2024)
This research aims to examine the effectiveness of the Discovery Learning model in improving learning outcomes on style material in Class IV at SD Negeri 106156 Klumpang. A quasi-experimental method with a pretest-posttest control group design was employed. The experimental group consisted of 20 students using Discovery Learning, while the control group included 20 students taught using the lecture method. A 25-item multiple-choice test was used as the instrument to measure learning outcomes. Data were analyzed using the t-test. The post-test results showed that the experimental group had an average score of 81.9, while the control group had an average of 72.2. The t-test result (tcount = 7.726) was greater than ttable (2.10092), indicating a significant difference between the two groups. The improvement in the experimental group's pretest-posttest score was 19.6, compared to 9.4 in the control group. These findings suggest that the Discovery Learning model is more effective in enhancing students' learning outcomes than the lecture method.